Perilaku Guru Dalam Pembelajaran Berbasis Nilai Ibadah Di SMP IT Nurul Ilmi Medan Estate - Rini Rini Dewi Andriani (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2020)
Based on Law no. 20 of 2003 article 3 concerning the National Education System that national education functions to develop capabilities and shape the character and civilization of a dignified nation in the context of educating the nation's life, aiming to develop the potential of students to become human beings who believe and fear God Almighty, have noble character. , healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. Integrated Islamic School (SIT) is more dominant in its religious character education. One of the schools that has implemented religious character education through school culture is SMP IT Nurul Ilmi Medan Estate. It can be seen in the vision of this school, namely "Forming a Generation of Superior Muslims who Think, Think and Have Morals". This research was carried out with the aim of describing the implementation of worship value-based learning at SMP IT Nurul Ilmi Medan Estate. This type of research is descriptive research with a qualitative approach. Based on the results of research and discussion, it can be concluded as the implementation of teacher behavior through worship value-based learning at SMP IT Nurul Ilmi Medan Estate that the physical education component supports the implementation of worship value-based learning at SMP IT Nurul Ilmi Medan Estate